2011
DOI: 10.1016/j.immuni.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell and Macrophage Heterogeneity In Vivo

Abstract: Macrophage and dendritic cell (DC) are hematopoietic cells found in all tissues in the steady state that share the ability to sample the environment but have distinct function in tissue immunity. Controversies remain on the best way to distinguish macrophages from DCs in vivo. In this Perspective, we discuss how recent discoveries in the origin of the DC and macrophage lineage help establish key functional differences between tissue DC and macrophage subsets. We also emphasize the need to further understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
372
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 336 publications
(385 citation statements)
references
References 143 publications
9
372
0
1
Order By: Relevance
“…103 Preclinical and translational advances. Within the abundant preclinical literature that has been published during the last 13 months on ICD-inducing chemotherapeutics, we found of particular interest the works of: (1) Pallasch and colleagues (Massachusetts Institute of Technology; Cambridge, MA, US), who demonstrated that cyclophosphamide induces an acute secretory phenotype in malignant cells, stimulating the release of various immunostimulatory cytokines that promotes a macrophagedriven, tumor-targeting innate immune response; [104][105][106] (2) Tavora and collaborators (Barts Cancer Institute; London, UK), who showed that the inhibition of protein tyrosine kinase 2 (PTK2, also known as FAK) [107][108][109] in the endothelial tumor [130][131][132][133] in the establishment of a collagenenriched tumor microenvironment contributing to the resistance of (at least a subset of) breast carcinomas to doxorubicin. 134 Recently initiated clinical trials.…”
Section: Update On the Development Of Icd-inducing Chemotherapeuticsmentioning
confidence: 99%
“…103 Preclinical and translational advances. Within the abundant preclinical literature that has been published during the last 13 months on ICD-inducing chemotherapeutics, we found of particular interest the works of: (1) Pallasch and colleagues (Massachusetts Institute of Technology; Cambridge, MA, US), who demonstrated that cyclophosphamide induces an acute secretory phenotype in malignant cells, stimulating the release of various immunostimulatory cytokines that promotes a macrophagedriven, tumor-targeting innate immune response; [104][105][106] (2) Tavora and collaborators (Barts Cancer Institute; London, UK), who showed that the inhibition of protein tyrosine kinase 2 (PTK2, also known as FAK) [107][108][109] in the endothelial tumor [130][131][132][133] in the establishment of a collagenenriched tumor microenvironment contributing to the resistance of (at least a subset of) breast carcinomas to doxorubicin. 134 Recently initiated clinical trials.…”
Section: Update On the Development Of Icd-inducing Chemotherapeuticsmentioning
confidence: 99%
“…Several reports have also argued against a replacement of adult microglia by circulating myeloid (Crocker and Gordon, 1989;Flotte et al, 1983) Table summarizes markers of macrophages in the spleen, lymph node, lung, and liver and of microglia in the CNS (Hashimoto et al, 2011b). precursors under physiological conditions (Ajami et al, 2007;Becher et al, 2001;Greter et al, 2005;Mildner et al, 2007).…”
Section: Turnover Of Microglia In the Steady Statementioning
confidence: 99%
“…27). Regardless of their localization, DC subsets act in a coordinated fashion to bridge innate and adaptive immune responses in health and disease.…”
Section: Cd103mentioning
confidence: 99%